Managing Stormwater: Practices and Challenges for Reuse and Recycling - Anwar, Faisal (2019)
This book has eleven chapters that describe the practices and challenges of different BMPs for stormwater management. These include combined sewer networks, different rainwater harvesting techniques, constructed wetlands, MUSIC modelling of bioretention systems, catch basin inserts, permeable pavements, the use of adsorbents for cleaning stormwater, low impact developments, and membrane-based technologies for stormwater treatment.